INFORMATION AND REFERRAL NEEDS FOR CARE PARTNERS OF ADULTS WITH ALZHEIMER'S DISEASE IN RURAL AND REMOTE COMMUNITIES. (11th November 2018) - Longstreth, M; Slosser, A; Barry, R; Carrico, C; McKibbin, C
Abstract: For persons living with Alzheimer's disease and related dementias (ADRD), access to adequate information about support services is crucial to aging in place. The need is particularly relevant for those in rural regions where support services may be more scarce and at greater distances. To develop a rich understanding of the needs for information and referral that exist in rural and remote areas, a series of town hall focus group meetings were conducted in a frontier state. Focus group were led by an expert facilitator and were open to professionals and the public. Audio recordings were created, transcribed, and coded for common themes following procedures of Zuckerman-Parker and Shank (2008). Participants were 175 adults who were, on average, 59.32 years of age (SD = 14.91). A majority was Non-Hispanic White (n = 157; 98.1%) and female (n = 126; 73.7%). Over one-third identified as being a caregiver (n = 62; 35.6%). Three primary themes emerged as areas of improvement: (1) the need for better information and referral content, (2) confusion about where to turn for information, and (3) preferred methods of information delivery. Existing community resources and funding support should be leveraged to provide multiple points of access to reliable information. Marketing campaigns should also be developed to eliminate confusion about how and where to access information and services.